(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Dental trauma poses a significant risk of infection due to tissue damage, exposure to oral microorganisms, and compromised immune responses. Prompt evaluation, appropriate wound management, and preventive measures are essential to minimize the risk of infection and promote optimal healing following dental trauma. This abstract provides an overview of the risk factors associated with post-traumatic infections and emphasizes the importance of timely intervention and adherence to evidence-based guidelines in preventing complications. Close monitoring of patients following trauma, especially those with compromised immune systems or concomitant injuries, is necessary to detect early signs of infection and initiate appropriate treatment promptly. The references cited in this abstract provide comprehensive insights into the management of dental trauma and the prevention of associated infections, serving as valuable resources for dental practitioners and healthcare professionals involved in the care of patients with traumatic dental injuries.